Eksperiment v splošni anorganski kemiji: Navodila - Slemnik, Mojca; Ban, Irena; Kristl, Matjaž; Stergar, Janja (University of Maribor Press, 2022)
Experiments in General and Inorganic Chemistry: Instructions. This work is a collection of instructions for conducting practical experiments in general and inorganic chemistry. Students learn the basics of experimental work in the laboratory: They get to know the laboratory inventory, master the basic laboratory techniques and extend them with regard to setting up apparatus for chemical experiments, link arithmetic problems to experiments, learn to write reports and learn about safety in the chemical laboratory.